IMPLEMENTASI MEDIA ANIMASI DALAM MENINGKATKAN AKTIVITAS PEMBELAJARAN DAN PRESTASI BELAJAR - Purni, Ida Ayu (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
This research aims to provide a description of the application of animation media in learning Hindu Religious Education at SDN 2 Sokong. This research uses Classroom Action Research (CAR), which is to address real problems experienced by teachers and students in the classroom, especially Hindu Religious Education lessons. Researchers as implementers and observers looked at the active learning of 21 students for the 2023/2024 academic year. Data collection by observation and interviews. The data obtained was analyzed descriptively and presented in the form of tables and diagrams. The research results showed that animation media was able to increase student activity during learning by 17 percent and the first cycle student learning outcomes reached 30 percent who obtained a score above 90 with an average score of 83.85. The learning process using animation media resulted in an increase in learning outcomes, namely reaching 76 percent with a score above 90 or an average of 94.19 in the second cycle. Thus, the use of animated learning media increases learning activities and learning achievement in Hindu Religious Education at SDN 2 Sokong.